Research on Turning Ability of High-speed Maglev Train - 王汝宁; 程虎; 李云钢 (机车电传动)
Three chief factors had been analyzed: the length of guidance electromagnet, range of motion and pulling force of pendulum pole, adjacent bogie squeeze and stretch on the joint electromagnet. And based on the analysis, improved scheme was proposed. By keeping train tilting structune removing joint electromagnet, moderately reducing the length of bogie and guiding electromagnet, the improved vehicles can meet the requirement of smaller turning radius.